ChemInform Abstract: Me3N‐Promoted Synthesis of 2, 3, 4, 4a‐Tetrahydroxanthen‐1‐one: Preparation of Thiosemicarbazone Derivatives, Their Solid State Self‐Assembly and Antimicrobial Properties. Issue 14 (March 2016) - Hameed, Aminah; Shafiq, Zahid; Yaqub, Muhammad; Hussain, Mazhar; Hussain, Muhammad Ajaz; Afzal, Muhammad; Tahir, Muhammad Nawaz; Naseer, Muhammad Moazzam
Abstract: The title compound (III) is synthesized in high yield by Me3 N‐promoted domino Baylis—Hillman/oxa‐Michael reaction sequence and smoothly converted into xanthene‐based thiosemicarbazones (V).